Private Saving and Terms of Trade Shocks : Evidence From Developing Countries - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1991)
This paper examines the relationship between temporary terms of trade shocks and household saving in developing countries. It is first shown that, from a theoretical standpoint, this relationship is ambiguous: private saving may rise or fall in response to a transitory terms of trade shock, depending on the values of the intertemporal elasticity of substitution and the intratemporal elasticity of substitution between traded and nontraded goods. Empirical estimates of these two parameters are obtained using data from a sample of 13 developing countries, and then used to draw implications for the response of private saving to transitory terms of trade shocks.